Creative Fusion: Exploring the Convergence of Art, Science, and Education in Traditional Crafts through Bird-Inspired Design Techniques - Kim, Namsoo Peter; Park, SUJI; Kim, Yikyong; Kim, Boyong; Song, ChahngBaek; Song, Narae (International Journal of Arts, Sciences and Education, 2023)
This paper highlights how, over the past 12 years, we have effectively applied the bird-inspired technique of VIZO design to create unique 3D products by filling three-dimensional voids and materials with continuous lines. It presents the possibilities of combining art and modern technology in a traditional craft and emphasizes the concept of creative fusion, which is material-independent and can convey emotion through a variety of media. The educational program leverages the interdisciplinary strengths of science, engineering, and art to make it accessible to the public, students, and professionals without prior artistic training. Students learned how to research and explore the creative intersection of science and art for educational purposes—an area that is often challenging for the general public due to limited access to materials such as biomaterials or hemp, as well as the use of equipment that is complicated to operate. The combination of modern technology and traditional art has opened up new avenues of creativity and self-expression. This paper is a first-hand account of the fusion of art and science in an interdisciplinary curriculum and the resulting final artwork. It presents an innovative attempt to combine traditional materials such as hemp with state-of-the-art 3D printing technology and successfully demonstrates the fusion of science and art.